Ответы и объяснения

Лучший Ответ!
2011-12-15T18:06:54+04:00

х+56=95    у-67=41   86-z=39      (68-m)+16=24     85-(14+n)=68
х=95-56    у=41+67   z=86-39      68-m=24-16        14+n=85-68
х=39         У=108      z=47           68-m=8              14+n=17

                                                 m=68-8              n=17-14

                                                 m=60                 n=3

2011-12-15T18:07:13+04:00

1. х+56=95                                       

х=95-56

х=39

2. у-67=41

у=41+67

у=108

3. 86-Z=39

z=86-39

Z=47

4. (68-m)+16=24 

(68-m)=24-16

68-m=8

m=60

5. 85-(14+n)=68

14+n=85-68

14+n=17

n=3